Impact of care guilt on the health status of female medical staff: a cross-sectional study - Jia Xu; Chun Xia (International Journal for Equity in Health)
Abstract Background In this study, we explored changes to female medical staff’s health status under the influence of care guilt in the process of balancing work and family care responsibilities. The mediating role of time pressure within this nexus was examined, and an ideal concept derived from the Confucian cultural context, “Zhong-yong,” was investigated as a moderator of the impact of care guilt on health status. Method A questionnaire survey of 407 full-time female medical staff with family care needs, recruited using convenience sampling from eight hospitals in China, was conducted. The survey tools comprised the Relationship Guilt Scale, Dapkus’ time pressure scale, Zhong-yong scale, and Self-rated health status scale. A moderated mediation model was established to test the hypotheses. Results Care guilt had a significant negative impact on health condition after controlling for variables such as age, educational level, and professional position. Time pressure mediated the association between care guilt and health status. Zhong-yong levels moderated the effects of care guilt on time pressure and had a direct effect on health condition. Care guilt weakened health condition, partly through the experience of time pressure. However, low levels of Zhong-yong predicted a greater negative impact of care guilt on health condition. Conclusion Female medical staff require a comprehensive approach to balancing their work and family responsibilities to mitigate their experience of guilt and poor health.